2016
DOI: 10.1021/acsami.6b04591
|View full text |Cite
|
Sign up to set email alerts
|

Lentinan-Modified Carbon Nanotubes as an Antigen Delivery System Modulate Immune Response in Vitro and in Vivo

Abstract: Adjuvants enhance immunogenicity and sustain long-term immune responses. As vital components of vaccines, efficient adjuvants are highly desirable. Recent evidence regarding the potential of carbon nanotubes (CNTs) to act as a support material has suggested that certain properties, such as their unique hollow structure, high specific surface area, and chemical stability, make CNTs desirable for a variety of antigen-delivery applications. Lentinan, a β-1,3-glucohexaose with β-1,6-branches that is extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Such functionalization has reduced their cytotoxicity and altered the function of immune cells, such as PEG and polyethylenimine (PEI), 76 cationic glycopolymers, 77 vinblastine, 78 and Lentinan. 79 Huang et al reported good results using mice-bearing syngeneic murine squamous cell tumors. They intratemporally injected single-walled CNTs (SWCNTs) and irradiated the cancer cells with a low power NIR laser for 10 minutes.…”
Section: Cntsmentioning
confidence: 99%
“…Such functionalization has reduced their cytotoxicity and altered the function of immune cells, such as PEG and polyethylenimine (PEI), 76 cationic glycopolymers, 77 vinblastine, 78 and Lentinan. 79 Huang et al reported good results using mice-bearing syngeneic murine squamous cell tumors. They intratemporally injected single-walled CNTs (SWCNTs) and irradiated the cancer cells with a low power NIR laser for 10 minutes.…”
Section: Cntsmentioning
confidence: 99%
“…Various β-glucans have been extracted from sources such as cereals, yeast, bacteria, and fungi 5 . Among β-glucans, lentinan is extracted from bodies of shiitake ( Lentinus edodes ) and is a high molecular weight polysaccharide 2, 6 . Lentinan, a well known biological response modifier, has a β-(1 → 3) linked backbone and two β-(1 → 6) side chains every five residues 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Lentinan, a well known biological response modifier, has a β-(1 → 3) linked backbone and two β-(1 → 6) side chains every five residues 2 . Lentinan enhances the cytotoxic activities of primary macrophages and RAW264.7 cell lines and was found to elevate cytotoxic activity and tumor necrosis factor (TNF) secretion in macrophages both in vitro and in vivo 2, 6 . In addition, lentinan has been shown to increase peritoneal macrophage cytotoxicity against metastatic tumors 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Another classical approach is to directly bind surfactants, nucleic acids, peptides, polymers or oligomers in a non‐covalent manner . Recently, there have also been reports on the use of carbon nanotubes for the delivery of antigens, but most of them just modified simply to increase their water solubility, which makes them less effective in antigen delivery …”
Section: Introductionmentioning
confidence: 99%
“…[23][24] Recently, there have also been reports on the use of carbon nanotubes for the delivery of antigens, but most of them just modified simply to increase their water solubility, which makes them less effective in antigen delivery. [25][26][27] In this study, we developed multi-walled carbon nanotubes (MWCNTs) modified with mannose (Man-MWCNTs) as a specific target delivery system to DCs. Compared with passive target delivery, decorating with targeting ligands which can actively recognize specific receptors on the target cell is much more efficient.…”
Section: Introductionmentioning
confidence: 99%